Judging anomalies at the 2010 Olympics in men`s figure skating - Looney, M. (Research Quarterly for Exercise and Sport, 2011)
Intraclass correlation coefficients and a modified Bland-Altman analysis provide incomplete information about judge behavior. They cannot identify anomalies in judges` individual scoring patterns. A many-facet Rasch analysis has been recommended as a way to identify these anomalies (Looney, 2004). The purpose of this study was to use a many-facet Rasch analysis to determine if there were anomalies in judges` scoring patterns for men`s figure skating at the 2010 Olympics. Nine judges` scores, retrieved from the Internet, were analyzed after receiving approval from the Office of Research Compliance. Judges` free skate scores for each of five program components (choreography, interpretation, performance, skills, and transitions) for 24 skaters were analyzed using a three-facet Rasch rating scale analysis (skater by program component by judge). Plushenko was the only one of the top three skaters overall to have unexpected scores (standardized residual > |2|). The scores given to Plushenko did not fit the model well (Outfit MNSQ statistic = 2.67; Estimated Discrimination Index = -0.69). Judge 1 scored Plushenko much higher than Lysacek (first place) when the model expected these skaters to receive the exact same scores (p = .05; differential judge functioning). Judge 2 gave Plushenko about 1.25 points higher than expected scores for interpretation and performance while scoring Transitions lower than expected by 2 points. Plushenko`s overall free skate score represents a different construct than the scores do for the other skaters. Skating officials should investigate the unexpected scores given to Plushenko by Judges 1 and 2 for possible reasons (e.g., nationalistic bias).